Accidental activists: headhunters as marginal diversity actors in institutional change towards more women on boards - Doldor, Elena; Sealy, Ruth; Vinnicombe, Susan (Wiley, 2016)
We present a qualitative study that examines the role of headhunters as actors in a broader institutional change process aiming to increase gender diversity on corporate boards. We draw on institutional and diversity management theories to conceptualise their change agency in the broader field of women on boards. We describe their role as ‘accidental activists’ and theorise two micro-processes that define their change agency in this field: voluntaristic framing of intentionality and role redefinition by drawing on competing logics. This conceptualisation does not match the heroic image of the institutional entrepreneur driving institutional change, or that of the tempered radical championing diversity, but rather casts light into a marginal and previously neglected change role. We demonstrate the opportunistic and precarious nature of this role with regard to both institutional change and diversity management and discuss its possibilities and perils.
Keywords: Institutional change; Change agency; Women on boards; Diversity management; Headhunters